From Fragmentation to Unification : The GST Impact on India’s State Indirect Tax Revenue Using Dynamic Panel Analysis - Jain, Khushboo; Singh, Shveta (Prabandhan: Indian Journal of Management, 2026)
Purpose : This research examined the influence of Goods and Services Tax (GST), sectoral composition, government expenditure, fiscal transfers, and the COVID-19 recovery period on indirect tax revenue across Indian states. Design/Methodology/Approach : The research employed a quantitative panel-data approach. Annual data from 27 Indian states were collected from 2012–2013 to 2022–2023. The outcomes were drawn from the application of the system generalized method of moments (GMM) approach to a dynamic panel model. Findings : The results revealed that the agricultural sector, manufacturing sector, service sector, development expenditures, GST implementation, and the COVID-19 recovery period positively influenced indirect tax revenue but were negatively influenced by fiscal transfers. Furthermore, a positive association was observed between the lag and current indirect tax revenue levels. Practical Implications : The findings suggested that policymakers should strengthen GST compliance mechanisms, promote formalization, incentivize productive expenditure, and reduce excessive dependence on central transfers to improve tax mobilization capacity across states. Originality/Value : This research is among the first to jointly examine the effects of the GST, sectoral composition, government expenditure, fiscal transfer, and the COVID-19 recovery period on indirect tax revenue at the Indian state level using a dynamic panel approach.